Giant Isolated Omphalocele: Role of Prenatal Diagnosis in Prognostic Asessment and Perinatal Management - A. M. Cubo; M. V. Lapresa Alcalde; I. Gastaca; M. O. Rodríguez-Martín; M. C. Martín Seisdedos; M. V. R. Velasco Ayuso; R. C. Cebrián Muiños; J. M. Sayagués (Case Reports in Medicine)
Omphalocele is a congenital malformation of the abdominal wall consisting of a protrusion of the abdominal contents at the base of the umbilical cord. It has a high association with genetic and structural defects; however, if the latter is ruled out, its prognosis improves significantly. Prenatal diagnosis has a key role in this condition as omphalocele can be diagnosed by ultrasound in the first trimester scan, enabling a coordinated approach strategy to achieve the best perinatal results. We present a case report of a pregnant patient with a fetus having a giant omphalocele in which prenatal diagnosis played a decisive role, allowing the coordination of a multidisciplinary team, which was crucial in the immediate care of the newborn.